UJI AKTIVITAS ANTIOKSIDAN MENGGUNAKAN RADIKAL 1,1-DIFENIL-2-PIKRILHIDRAZIL (DPPH) DAN PENETAPAN KANDUNGAN FENOLIK TOTAL FRAKSI ETIL ASETAT EKSTRAK ETANOLIK DAUN BENALU (Dendrophthoe pentandra L. Miq.) YANG TUMBUH DI POHON KEPEL (Stelechocarpus burahol (Bl.) Hook. f.) - Willigis Danu Patria; C.J. Soegihardjo (Universitas Sanata Dharma, 2013)
Abstract: Antioxidant has the ability to capture free radicals. These free radicals can oxidize nucleic acids, proteins, lipids or DNA, causing degenerative diseases. Antioxidants compound found in plants such as phenolic acids, polyphenols and flavanoids would capture free radicals such as peroxide, hydroperoxide or lipid peroxyl and also inhibit the oxidative mechanisms that show degenerative diseases. Quercetin and quercetin 3-o-rhamnosida as constituents of mistletoes (Dendrophthoe pentandra (L.) Miq.), are able to provide antioxidant activity. Mistletoes dried and extracted with 70% ethanol, followed by fractionation with ethyl acetate. Antioxidant activity of ethyl acetate fraction from ethanol extract was calculated using DPPH method and obtained IC50 values. The results showed that the ethyl acetate fraction from ethanolic mistletoes leaf extract has antioxidant activity with IC50 value of (12.57 ± 0.7) mg / mL. The content of total phenolic (13.76±0.9) mg gallic acid equivalents per gram of ethyl acetate fraction from ethanol extract of leaves of the mistletoes. Keywords: Antioxidant, misletoes leaf, Dendrophthoe pentandra, ethyl acetate fraction, ethanolic extract, DPPH, total phenolic..